Software Defined Networks Security: Link Failure Analysis in SDN - R.Badlishah, Ahmad; Al-Junaid, M.A.H; Mohd Warip, M.N; Mat Safar, A; Zunaidi, I; Khairunizam, W; Razlan, Z.M; Shahriman, A.B (2019)
SDN is the new network technology. Although SDN still new, it is inseparable from the issue of a link failure. By using SDN, link failure scenario can be simulated and collection of data can be analysed. Before creating link failure scenario, several topologies were needed to show similarities with traditional network. There are many topologies that can be created by using SDN because SDN already provide virtual network devices. Each network device will be build inside virtual network topology. With use of desired topology then link failure scenario can be implemented. SDN also need a controller that acts a "brain" to the network. The controller will be provide a routing algorithm to control the behaviour of the network when one or more links become fail to connect with host or controller. One of suitable controller was Ryu which can adapt to any traffic handler and already provide application resemble to network behavior. All software components will be simulated inside Mininet emulator, one of realistic virtual network application.